The Contribution of Tafsir Tarbawi in Shaping Student Morals and Ethics - H.Hamdan Fathurrohman N; Iskandar Mirza (Classroom: Journal of Islamic Education, 2025)
Tafsir Tarbawi plays an important role in forming student morals and ethics in the following ways: 1). Understanding Islamic Values, 2). Character Formation, 3). Increased Social Awareness, 4). Application of Ethics in Everyday Life, 5). Positive Mentality Development: Tarbawi interpretation teaches students to face challenges with a positive and hopeful attitude. This includes developing a mentality that encourages them to act with integrity and commit to good values. Thus, tarbawi tafsir not only functions as a source of religious knowledge, but also as an effective educational tool in shaping students' morals and ethics, making them noble and good-natured individuals, who can contribute positively to society. The implementation of tarbawi interpretation in character education is very important to create a generation of believers and noble morals.